Selective genetic analysis of p53 immunostain positive cells. Issue 3 (1st June 2000) - Phelps, M; Wilkins, B S; Jones, D B
Abstract : The isolation of p53 immunostain positive cells from histological sections for molecular genetic studies is a difficult task, especially if there are few positive cells. To eliminate contaminating DNA from p53 negative cells, which can obscure the results of molecular assays, a variation on the technique of immunohistoselective sequencing was developed. This is a highly selective approach, whereby immunostained sections of formalin fixed, paraffin wax embedded tissue are exposed to ultraviolet irradiation to damage the DNA in p53 negative cells. The DNA in positive cells remains unaffected because the dark immunostain protects their nuclei from ultraviolet light. Polymerase chain reaction single strand conformation polymorphism of samples enriched with p53 immunostain positive cells has shown that this method can produce pure samples of mutated DNA. The isolation of DNA from minority immunostain positive cells allows a wide range of molecular analyses to be carried out on these samples, which would otherwise be hampered by the problem of contaminating background cells.